Ready tp Read : Can a Cat Do That? - Carle, Eric (New York Simon Spotlight, 2018)
Shows different animals behaving as they normally do, such as running or pinching, and asks if a cat can do the same. Includes word list and follow-up questions.
Keywords: Cats -- Juvenile fiction -- Habits and behavior; Animals -- Juvenile fiction -- Habits and behavior; Cats -- Fiction -- Habits and behavior; Animals -- Fiction -- Habits and behavior; Readers; Early readers